Konsep Kebijakan Pariwisata Berbasis Kerakyatan (Studi Pariwisata Di Pulau Lombok) - Usman Munir (Universitas Merdeka Madiun, 2022)
Abstract— The islands of Lombok and Bali have been designated as national tourism gateways in the MP3EI Corridor V (Masterplan for the Acceleration and Expansion of Indonesian Economic Development). Lombok Island, one of the national tourist destinations with the nickname Island of a Thousand Mosques, has a very diverse and potential tourist attraction. The choice to develop tourism does not always have a positive impact on the community, so a policy concept is needed which is expected to provide positive changes and impacts on the people of Lombok in particular and Indonesia in general. This article is an empirical normative research, meaning that the problems raised, discussed and described in this study are focused on the application of rules or norms in positive law and seeing phenomena in the field. This type of normative juridical research is carried out by examining various kinds of formal legal rules such as laws, literature which are theoretical concepts which are then linked to the problems that are the subject of discussion. The results of this study are to formulate the concept of people-based tourism, namely firstly the presence of policies that are prosperous, secondly policies that protect local wisdom, thirdly policies that protect community participation, fourthly policies that limit foreign investment, fifth, namely policies that optimize corporate social responsibility (CSR). )for tourism development.